The Effect of ReadToMe Application on Reading Fluency and Motivation in Narrative Texts - Agitha Ramadhani Riasang; Ridwan Ridwan; Adi Isma; Dwi Adi Nugroho; Nur Husnil Khatimah (GLENS: Global English Insights Journal, 2025)
This quasi-experimental study examined the effect of the ReadToMe application on reading fluency and motivation among eighth-grade Indonesian EFL learners. Twenty-six students from SMP Negeri 1 Tutallu were randomly assigned to experimental (n=13) and control (n=13) groups. The experimental group received instruction using the ReadToMe application with narrative texts, while the control group followed conventional textbook-based methods over six weeks. Reading fluency was assessed through pre-test and post-test measurements using validated rubrics evaluating accuracy, pronunciation, and intonation. Student motivation was measured post-intervention through a 15-item Likert-scale questionnaire examining five dimensions: curiosity, challenge, grades, involvement, and competition. Results revealed significant improvements in the experimental group, with mean scores increasing from 45.85 to 76.00 (N-Gain=0.5484), compared to the control group's increase from 46.31 to 56.77 (N-Gain=0.2015). Independent samples t-test confirmed statistical significance (p<.001) with a very large effect size (Cohen's d=2.67). Questionnaire analysis indicated high motivation levels (80.00%) among experimental group students. These findings suggest that the ReadToMe application effectively enhances both reading fluency and motivation in narrative text instruction, offering practical implications for EFL teachers seeking technology-integrated approaches to address reading challenges in Indonesian educational contexts.